Effects of grazing on the growth and development of white clover (Trifolium repens L.) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science at Massey University - Pascoe, William Blamires (Massey University, 1973)
White Clover (Trifolium repens L.) has been a part of the pasture scene for many years (Erith 1924; Stapledon 1919-1928) and its distribution in temperate regions is world wide (Erith loc. cit.). Its value both as a legume contributing to the nitrogen cycle (Sears 1953) and as a forage for animals has long been recognised (Erith loc. cit.) and these are still the main reasons for its continued valuable contribution to temperate pastures today (Williams 1970). In the N.Z. grassland scene its continued contribution in the future has been emphasised (Watkin 1972). Dry matter production per se is not a sufficiently accurate measure of the excellence of white clover (Cooper 1970). Particular attention in recent years has been paid to the reasons for the high nutritive value of white clover (Ulyatt 1971) which has been shown, on many occasions, to be superior to the ryegrasses in terms of liveweight gain (Joyce and Newth 1967; Ulyatt 1969) and in combination with the ryegrasses has been shown to enhance their nutritive value (Rae et al 1963; Rattray and Joyce 1969).
Keywords: White clover; Growth